Cryptosporidiosis: Environmental, therapeutic, and preventive challenges - Collinet-Adler, Stefan (2010)
Cryptosporidium spp. are responsible for endemic and epidemic disease worldwide. Clinical manifestations may include acute, persistent, or chronic diarrhea, biliary, and pulmonary disease. Disease severity ranges from asymptomatic or mild to severe, intractable diarrhea with wasting depending on immune status, nutrition, and age. Transmission is fecal-oral with both human and animal reservoirs. Disease is often self limited in healthy individuals, but therapy remains a challenge in the immune-compromised. Prevention currently depends on appropriate hygiene and proper water management and treatment.